Petroleum reservoir analogues - Ganat, T.A.-A.O. (Springer, 2020)
Obtaining geophysical data is a time consuming and costly activity. Also, depending on the exploration stage, there is few data available and it is not even possible to obtain new data (for the duration of the bidding phase). One of the general strategies in the industry is to use existing known information from similar reservoirs (analogues) to better determine the missing data, to get more information about the target area. Therefore, the technical team, geologist and reservoir engineers must evaluate all accessible data types such as seismic, well logs, well testing, production data, cores and analogues data available, to make the best technical and business decisions in exploration and production operations process. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.